The effect of seawater on the corrosion behavior of natural gas pipelines in Malaysia - Suziee, Sukarti (2013)
Seawater is inherently chemically aggressive, complex fluid that affects nearly all structural materials to some extent. Corrosion in the seawater is dependent on a number of factors such as material composition, water chemistry, pH, biofouling, microbiological organisms, pollution and contamination and temperature. Understanding how these factors may affect corrosion in seawater can support the design of materials, components, and systems for optimal service performance and structural life. A study was taken to investigate the effect of different seawater surrounding Peninsular Malaysia on the carbon steel having app1ication as petroleum/natural gas pipeline. The Tafel Extrapolation technique has been applied to evaluate the corrosion rate of the carbon steel and different locations of natural seawater have been used as the electrolyte solution. In this experiment, Carbon steel API SL X42 were utilized and the seawater is taken from the South China Sea and Strait of Malacca. Beside the corrosion rate calculating the type of corrosion attack has also been discussed on the basis of the morphology and the content properties of seawater are determined. It is found that the corrosion rate of the carbon steel specimen is significantly nobler· in-the-Strait of Malacca Sea than that in the south China Sea. The results varied from 0.01 to 0.025 mm/year. Immersion test of two hours and ten days were carried out to determine the corrosion product that formed at the surface of pipe. Localized corrosion (pitting) and uniform corrosion attacked the surface specimen severely for each sea. The lower corrosion rate is achieved with higher contents of sodium chloride and salinity. Some of the dissolved material such as Iron oxide also distributes to the formation 0f corrosion. Generally from the result, South China Sea is more favorable in the applicationof this material even though the material is acceptable in both seas.